Features, Analysis Techniques, and Detection Methods of Cryptojacking Malware: A Survey - Kadhum, Laith M; Firdaus, Ahmad; Hisham, Syifak Izhar; Mushtaq, Waheed; Ab Razak, Mohd Faizal (JOIV : International Journal on Informatics Visualization, 2024)
Various types of malwares are capable of bringing harm to users. The list of types are root exploits, botnets, trojans, spyware, worms, viruses, ransomware, and cryptojacking. Cryptojacking is a significant proportion of cyberattacks in which exploiters mine cryptocurrencies using the victim’s devices, for instance, smartphones, tablets, servers, or computers. It is also defined as the illegal utilization of victim resources (CPU, RAM, and GPU) to mine cryptocurrencies without detection. The purpose of cryptojacking, along with numerous other forms of cybercrime, is monetary gain. Furthermore, it also intended to stay concealed from the victim's viewpoint. Following this crime, to the author's knowledge, a paper focusing solely on a review of cryptojacking research is still unavailable. This paper presents cryptojacking detection information to address this deficiency, including methods, detection, analysis techniques, and features. As cryptojacking malware is a type that executes its activities using the network, most of the analysis and features fall into dynamic activities. However, static analysis is also included in the security researcher’s option. The codes that are involved are opcode and JavaScript. This demonstrates that these two languages are vital programming languages to focus on to detect cryptojacking. Moreover, the researchers also begin to adopt deep learning in their experiments to detect cryptojacking malware. This paper also examines potential future developments in the detection of cryptojacking.